Recent advances in microwave-absorbing materials fabricated using organic conductive polymers - Peymanfar, Reza; Dogari, Haniyeh; Selseleh-Zakerin, Elnaz; Hedayatzadeh, Mohammad Hossein; Daneshvar, Sara; Amiri-Ramsheh, Nasim; Ghafuri, Hossein; Mirkhan, Ali; Ji, Guangbin; Aslibeiki, Bagher (Frontiers in Materials, 2023)
Microwave-absorbing materials are widely utilized in military and civilian applications. Moreover, their environmental potential to refine electromagnetic pollution has promoted their importance. An ideal conjugated organic polymer for use as a microwave-absorbing material should possess high porosity, low density, a long conjugated backbone, a narrow energy band gap, proper conductive and relaxation loss, and vast specific surface area. This review describes the conductive polymer types used as microwave-absorbing material and their composites toward improving microwave-absorbing capability. Additionally, recent developments in synthetic strategies and structural properties of pure carbon-based microwave-absorbing materials and other conjugated structures having heteroatoms in their chains are discussed. In the field of microwave absorbers, the predominant microwave-absorbing mechanisms among conductive polymers and their composites as well as the special mechanisms for tuning microwave-absorbing characteristics, including metamaterial and quasi-antenna features, are dissected. This review sheds new light on architecting low-density and high-performance microwave-absorbing structures and offers new prospects in tailoring conjugated polymers based on their dominant mechanisms.